Evaluating Safer Conception Options for HIV-Serodiscordant Couples (HIV-Infected Female/HIV-Uninfected Male): A Closer Look at Vaginal Insemination - Okeoma Mmeje; Craig R. Cohen; Deborah Cohan (Hindawi Limited, 2012)
HIV serodiscordant couples represent at least half of all HIV-affected couples worldwide. Many of these couples have childbearing desires. Safer methods of conception may allow for pregnancy while minimizing the risk of sexual transmission of HIV. In serodiscordant partnerships with an HIV-infected female and HIV-uninfected male, vaginal insemination of a partner's semen during the fertile period coupled with 100% condom use may be the safest method of conception.